GENEOLOGI GERAKAN PROFETIK MUHAMMADIYAH DI DESA KARAMA BURA - Ismail, Azhar; Rizki; Jalaluddin; Hendra; Ihlas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the genealogy, values, practices, and implications of the Muhammadiyah prophetic movement in the socio-religious life of the Karama Bura Village community in Dompu. This study uses a qualitative approach with a historical-sociological design to trace the emergence and development of the Muhammadiyah movement at the local level and the dynamics of its interaction with the social and cultural structures of the village community. Data were collected through in-depth interviews with Muhammadiyah and community leaders, participant observation, and documentation studies of archives and related literature. Data analysis was conducted interactively through the stages of data condensation, data presentation, and conclusion drawing. The results indicate that the Muhammadiyah prophetic movement in Karama Bura Village in Dompu developed through a contextual process of adaptation and social construction. Prophetic values ​​based on transcendence, humanization, and liberation are manifested in persuasive and sustainable da'wah (Islamic proselytizing), education, and social activities. This movement has implications for social change in the form of strengthening the ethos of community independence and solidarity, religious change through the rationalization of worship practices, and cultural transformation toward progressive Islamic values. This research confirms that studying Islamic movements at the local level is crucial for understanding the dynamics of pluralistic, moderate, and transformative Indonesian Islam.